Women’s work: myth or reality? Occupational feminisation and job satisfaction in Australia - Dockery, Alfred Michael; Buchler, Sandra (My University, 2023)
Data on men and women’s job satisfaction conditional upon the degree of feminisation of their occupation are used to explore potential causes of occupational segregation by gender in the Australian labour market. We find some evidence for the notion of ‘women’s work’ – that certain occupations are highly feminised because women prefer the type of work done in those occupations. However, this primarily applies to mothers and the results also support the view that occupational segregation is generated by societal norms around roles allocated to men and women. In particular, patterns in satisfaction with hours of work and with pay in highly feminised occupations are consistent with mothers taking on the role of the ‘secondary breadwinner’. In contrast to suggestions in some of the existing Australian literature, the results also indicate that more highly feminised occupations are relatively poorly paid, other things held equal.
Australian Journal of Labour Economics
Keywords: Gender; Health and wellbeing; Identity; Labour market